The Development of Processed Coconut Products by Bungasire Savings Community Enterprise, Tha Klong Village, Pattani Province - Hayehama, Nipatimah (Journal of Liberal Arts Prince of Songkla University, 2023)
This research aimed to firstly explore Bungasire Savings Community Enterprise’s capabilities in processing coconut-based products, developing processed coconut products, and enhancing packaging for product value enhancement; and secondly identify approaches for marketing development. Purposive sampling was employed to select 53 members from the Bungasire Savings Community Enterprise, five coconut processing experts, and six packaging specialists. Data were collected through interviews and packaging assessment questionnaires, which were subsequently analyzed using descriptive statistics in percentage, mean, and standard deviation, complemented by an evaluation of product packaging. Findings revealed that the enterprise demonstrated consistent and positive development, emphasizing the use of local resource capital in its product development. Consequently, four new products were developed from processed coconuts, including coconut cooking oil, coconut balm, coconut yellow massage oil, and coconut facial serum. The development of the products also included secondary aspects such as logo and packaging design. This development aimed to increase product value and applied the 2S+2P model for marketing development, which included elements of 1) Storyline, to create brand narration or description; 2) Satisfaction, to ensure customers experience a feeling of worthiness and appreciation when using the product; 3) Promotional activities, to inform customers about the products and implement promotional activities; and 4) Partnership, to build marketing alliances. In conclusion, the results of this study indicated growth at the grassroots level of the economy and demonstrated the strength of community enterprise.